Information Governance Implications on Social Solidarity Economy - Fuzi Md Ajis, Ahmad; Md Jali, Jafalizan; Hajar Baharin, Siti; Khir Johari Abdullah Sani, Mad; ., . (International Journal of Engineering and Technology, 2018)
Social and Solidarity Economy (SSE) initiative which has been implemented in Malaysia and shows it success when four case studies reported SSE communities or organization displayed efforts in helping the public on exiting economic crisis. However, the information miss-governance destroys the SSE business value, slow down organization and creates unnecessary risk to the SSE communities when the government and state neglected SSE successful initiatives in combating economic crisis of the public, yet not having them as a solution to the economic downturn. A case study was conducted to identify implication of information governance towards social solidarity economy initiative. Information Governance Framework were tested to two focus group using empirical study. The framework was simulated on the focus group to analyze its significant impact. The results of the study indicates that information governance increase income generation with significant achievement. The results of this study is important to demonstrate application of IG towards SSE decreases opportunity of business operation mistakes and dark data composition.Â Â